Spatial variation characteristics of selected soils in the Tasik Chini watershed, Pahang, Malaysia - Islam, Mir Sujaul; Mohamad Idris, Ali; Noram Irwan, Ramli; Mohd Ekhwan, Toriman; Mohd Khairul Amri, Kamarudin; Hafizan, Juahir; Muhammad Barzani, Gasim (Science Publishing Corporation, 2018)
This study was carried out to assess the properties of soils in Tasik Chini watershed. Approximately 2741.52 ha of the total study area were selected for soil analyses. The physico-chemical properties and nutrient content were analyzed according to standard methods. The analyses showed that the sand dominant soil series were Serdang, Kuala Brang and Kekura series. The lowest sand content soil in both top soil and subsoil was Lating series (2.02% to 3.48%). On the other hand, the highest percentage (46.49%) of silt was measured in the Kedah soil series with the lowest value (17.71%) in the Kuala Brang series. The low pH value and low electrical conductivity was found in all studied soils. The results show that the cation exchange capacity (CEC) value of all top soils were comparatively higher than those of the subsoils. The mean CEC value of all the studied soil series was lower. The concentration of soil available phosphorus (P) and magnesium (Mg) of all the series were measured and categorized as low and very low, while the potassium (K) exchangeability of all series were higher. The obtained data indicated that some selected heavy metals were found in all the studied soils but did not exceed the normal stipulated levels.